IOT-BASED REMOTE MONITORING FOR RURAL AREAS: A LOW-COST PLATFORM FOR MATERNAL AND CHILD HEALTH (Eureka Journal of Computing Science & Digital Innovation, 2026)
The article proposes an IoT-based remote monitoring platform for maternal and child health in a rural area. This low-cost system incorporates several sensors, which monitor health parameters such as body temperature, heart rate, and environmental factors. Collected data is transmitted continuously to healthcare providers. The platform was intended to help promote early detection of health risks through continuous monitoring, and thus timely alerts reduce the mortality rate of mothers and infants, which is one of the prime challenges caused by limited health access in remote areas. This study demonstrates the feasibility, affordability, and effectiveness of IoT technology to improve health delivery in underserved communities.
Keywords: IoT, Remote monitoring, maternal health, child health, rural healthcare, low-cost platform, health sensors, real-time data, and telemedicine.